2008
DOI: 10.1128/jvi.00584-08
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Footprints of APOBEC3G on Hypermutated Human Immunodeficiency Virus Type 1 and Human Endogenous Retrovirus HERV-K(HML2) Sequences

Abstract: The human polynucleotide cytidine deaminases APOBEC3G (hA3G) and APOBEC3F (hA3F) are antiviral restriction factors capable of inducing extensive plus-strand guanine-to-adenine (G-to-A) hypermutation in a variety of retroviruses and retroelements, including human immunodeficiency virus type 1 (HIV-1). They differ in target specificity, favoring plus-strand 5GG and 5GA dinucleotide motifs, respectively. To characterize their mutational preferences in detail, we analyzed single-copy, near-full-length HIV-1 provir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
125
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(135 citation statements)
references
References 94 publications
(175 reference statements)
10
125
0
Order By: Relevance
“…Investigation of the sequences surrounding the edited nucleotides revealed dominance of adenosines at position + 2 relative to the editing site (GxA→AxA motif; the underlined G is the editing site; Methods and Supplementary Table S1). This is in agreement with previous experimental studies [14][15][16][17][18][19][20]23,24 and supports the identification of these mismatches as an outcome of mouse APOBEC3 activity.…”
Section: Identification Of Editing Sitessupporting
confidence: 93%
See 1 more Smart Citation
“…Investigation of the sequences surrounding the edited nucleotides revealed dominance of adenosines at position + 2 relative to the editing site (GxA→AxA motif; the underlined G is the editing site; Methods and Supplementary Table S1). This is in agreement with previous experimental studies [14][15][16][17][18][19][20]23,24 and supports the identification of these mismatches as an outcome of mouse APOBEC3 activity.…”
Section: Identification Of Editing Sitessupporting
confidence: 93%
“…This process is thus called DNA editing. In recent years, it was shown that active LTR (long terminal repeat) retrotransposons, which are endogenous retroviruses, can also be edited [14][15][16][17][18][19][20][21] . However, the impact of DNA editing on genome variability has not been explored to date 22 .…”
mentioning
confidence: 99%
“…Although that study confirmed the previously described bias toward G-to-A mutations in HIV-1 (30-32), APOBEC3G or APOBEC3F footprints could not be reliably detected. We previously determined the tri-and tetranucleotide target preferences for APOBEC3F and APOBEC3G (12), which enabled us to study the influence of the downstream nucleotide on Non-synonymous mutation…”
Section: Resultsmentioning
confidence: 99%
“…During reverse transcription, APOBEC3F and APOBEC3G induce cytidine-to-uridine (C-to-U) deamination of single-stranded minus-strand HIV-1 DNA, which generates guanosine-to-adenosine (G-to-A) mutations in plus-strand DNA (3,(5)(6)(7)(8)(9)(10)(11). These G-to-A mutations occur in APOBEC3F-and APOBEC3G-favored di-, tri-and tetranucleotide contexts (the GGnn-to-AGnn and GAnn-to-AAnn contexts, respectively [12]) (the mutated nucleotide residue is underlined). The remaining APOBEC3 proteins favor the same dinucleotide context as APOBEC3F.…”
mentioning
confidence: 99%
“…APOBEC3 genes are located on chromosome 22 [11] and these proteins acts upon viral nucleic acids as a form of intrinsic host defense [12]. A3 (APOBEC3) enzymes are capable of editing single-stranded DNA and recognize specific target sequences [13][14][15][16]. It plays an important role in the innate immune system and acts upon host defense against exogenous viruses and endogenous retro elements [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%